The Balance Between the Effectiveness and Safety for Chemotherapy-Induced Nausea and Vomiting of Different Doses of Olanzapine (10 mg Versus 5 mg): A Systematic Review and Meta-Analysis - Wang, Dong-Yang; Chen, Yi; Zhang, You; Shen, Ying-Qiang (Frontiers in Oncology, 2021)
Introduction： The aim of this study is to rigorously review the efficacy and safety of olanzapine in chemotherapy-induced nausea and vomiting（CINV） settings including (1) at 5 mg and 10 mg doses, and (2) the setting of highly emetogenic chemotherapy (HEC) and moderately emetogenic chemotherapy (MEC) Methods： Embase, Pubmed, and Cochrane Library were searched through April 18, 2021. The primary efficacy endpoints were the rate of complete response(CR; no emesis and no rescue), in the acute (0–24h post-chemotherapy), delayed (24–120h post-chemotherapy), and overall (0–120h post-chemotherapy) phases. The secondary efficacy endpoints were the rates of complete control (CC，no nausea and no emesis), for each phase. Safety endpoints were the rate of somnolence, as assessed by Common Terminology Criteria for Adverse Events (CTCAE) criteria. The Mantel-Haenszel, random or fixed-effects analysis model was used to compute risk ratios and accompanying 95% confidence intervals for each endpoint. For endpoints that statistically favored one arm, absolute risk differences were computed to assess whether there is a 10% or greater difference, used as the threshold for clinical significance by MASCC/ESMO. Result: Nine studies reported the use of 10 mg olanzapine to prevent CINV; three studies reported the use of 5 mg olanzapine to prevent CINV. When olanzapine was administered at 10 mg for HEC patients, 6 endpoints were statistically and clinically better than the control group. For MEC patients, 4 endpoints were better than the control group. When olanzapine is administered at 5 mg for MEC patients, 4 endpoints have statistical and clinical advantages.The sedative effects of olanzapine were significant than those of the control group. The sedative effect of the 10 mg olanzapine group was more significant than that of the 5 mg olanzapine group, both statistically and clinically. Conclusion: 5 mg olanzapine may be as effective as 10 mg olanzapine for patients with HEC and MEC, and its sedative effect is lower than 10 mg olanzapine. Fewer studies on 5 mg olanzapine have led to uncertain data. In the future, more randomized controlled trials of 5mg olanzapine are needed to study the balance between the effectiveness and safety of olanzapine.